It's About Ethics in Games Journalism? Gamergaters and Geek Masculinity. (September 2016) - Braithwaite, Andrea
#Gamergate is an online movement ostensibly dedicated to reforming ethics in video games journalism. In practice, it is characterized by viciously sexual and sexist attacks on women in and around gaming communities. #Gamergate is also a site for articulating "Gamergater" as a form of geek masculinity. #Gamergate discussions across social media platforms illustrate how Gamergaters produce and reproduce this gendered identity. Gamergaters perceive themselves as crusaders, under siege from critics they pejoratively refer to as SJWs (social justice warriors). By leveraging social media for concern-trolling about gaming as an innocuous masculine pastime, Gamergaters situate the heterosexual White male as both the typical gamer and the real victim of #Gamergate. #Gamergate is a specific and virulent online node in broader discussions of privilege, difference, and identity politics. Gamergaters are an instructive example of how social media operate as vectors for public discourses about gender, sexual identity, and equality, as well as safe spaces for aggressive and violent misogyny.